The additive effect of neuromuscular electrical stimulation and resistance training on muscle mass and strength - Narvaez, G.; Apaflo, J.; Wagler, A.; McAinch, A.; Bajpeyi, S. (European Journal of Applied Physiology, 2025)
Purpose To compare strength and muscle mass development between conventional resistance training (RT) and a combined resistance training with neuromuscular electrical stimulation group (RT + NMES).